AB0609 Fluorescence Optical Imaging of Inflammation in Systemic Sclerosis – A Pilot Study. (10th June 2014) - Pfeil, A.; Drummer, K.F.; Boettcher, J.; Jung, C.; Oelzner, P.; Wolf, G.
Abstract : Background: Systemic sclerosis is a connective tissue disease affecting various organs including the peripheral vessels resulting in Raynaud's phenomenon. For treatment of Raynaud's phenomenon the vasodilator Prostaglandin I2 analogue iloprost is widely used. An anti-inflammatory and immunmodulating effect is also described for iloprost. Fluorescence optical imaging (FOI) is an in vivo technique to visualize inflammation based on the accumulation of fluorescence optical contrast media (indocyanine green) in rheumatoid arthritis. Objectives: The aim of this study was to visualize inflammation using FOI in patients with Systemic Sclerosis (SSc) with SSc-related Raynaud's phenomenon depended and to clarify therapeutic response depending on the treatment with iloprost. Methods: 16 patients with SSc and Raynaud's phenomenon were prospectively included. The SSc patients were intravenously treated with over seven days. FOI (Xiralite system, Mivenion GmbH, Berlin, Germany) was performed at baseline and after seven days using on intravenous application of indocyanine green (ICG). Both hands were investigated, divided into 19 segments per hand (total 38 segments). Segments of both hands were quantitatively evaluated to determine enhancement of ICG. Results: In total 798 hand segments were scored considering all patients with SSc. At baseline 31.5% hand segments showed an ICG enhancement. The highest ICG enhancement was observed at the proximal phalanx of all fingers. After seven days of iloprost therapy a significant reduction of visible ICG enhancement was verified with -40.9% (p<0.001). Conclusions: The FOI technique seems to consists a high potential to visualize inflammation in patients with SSc and Raynaud's phenomenon. The anti-inflammatory effects of iloprost were detectable using the FOI based on the reduced enhancement of ICG. FOI offers a promising impact for the diagnosis and therapy monitoring of patients with SSc associated with Raynaud's phenomenon. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3271